MODEL "TEOPRENEUR": DESAIN KURIKULUM BERBASIS KOMPETENSI GANDA UNTUK LULUSAN TEOLOGI DI TENGAH TANTANGAN EKONOMI GLOBAL DAN DI INDONESIA - Margianto, Aris; Kustiadi, Josse (TEOLOGIS, RELEVAN, APLIKATIF, CENDIKIA, KONTEKSTUAL, 2026)
This study aims to develop a dual competency-based curriculum model called "Teopreneur," integrating theology and entrepreneurship within theological higher education in Indonesia. The issue addressed is the gap between theological education, which focuses on spiritual competencies, and the demands of the global-local economy requiring adaptive skills and financial independence for graduates. Employing a qualitative approach through a systematic literature review, data were collected from Scopus and Sinta-indexed journals and analyzed using thematic content analysis. The main findings yield two contributions: first, a dual competency matrix encompassing theological-leadership (60%), entrepreneurial (40%), and integrative domains; second, a 144-credit Bachelor of Christian Leadership curriculum design featuring an integrative structure through dual internships, capstone projects, and authentic assessment. This model expands the discourse on integrating faith and entrepreneurship as a holistic educational framework, while providing practical guidance for theological colleges to design contextual learning aligned with the Independent Learning-Independent Campus (MBKM) policy and Indonesia's people-based economy potential. The implications suggest this model can enhance graduate competitiveness, ministerial economic self-reliance, and the church's role in community socio-economic empowerment. Further research is needed to empirically test the model's validity and effectiveness.